Peningkatan Pengetahuan Masyarakat Tentang Kesehatan Lingkungan di RT 19 Kelurahan Sawah Lebar Baru Kota Bengkulu - Suryani, Ade Irma; Salma, Atika; Putri, Anisa Ika; Kartika, Dewi; Safitri, Devi; Hartati, Devi; Sari, Felia Novita; Sihombing, Ginna Veronica; Selviana, Indah; Sari, Nilam Kencana; Veronica, Syndi Ayu; Ningsih, Sunarti Maili; Yurnilawati, Yurnilawati; Novita, Vivin (Jurnal Pakar Pengabdian Kesehatan, 2025)
Environmental health is a crucial aspect in maintaining community quality of life, particularly in densely populated areas such as RT 19, Sawah Lebar Baru Village, Bengkulu. The lack of public knowledge regarding sanitation, waste management, and vector control contributes to the high risk of environment-related diseases. This Thematic Community Service Program (KKN-T) from Dehasen University Bengkulu aimed to evaluate the effectiveness of environmental health education in improving community knowledge and practices through environmental clean-up activities, distribution of educational leaflets, health counseling, and group discussions. The results revealed that the majority of the community initially had limited knowledge about environmental health. Implemented in the RT 19 residential area, the program demonstrated significant improvement in community awareness regarding environmental cleanliness. We recommend regular implementation of this education program by health workers and Posyandu cadres to achieve a healthy and self-reliant community.